FOOD SECURITY: ESSENCE OF THE NOTION - Vera A. Tikhomirova (Вестник Российского экономического университета имени Г. В. Плеханова)
In conditions of intense globalization of the world community the importance of the level of self-sufficiency in food is constantly growing. Protection of national and state interests in the field of food security is included in the complex of problems of national security and has become one of the most acute problems of the 21st century, which requires a thorough discussion in order to ensure security and real sovereignty of the Russian Federation. The author discloses the essence of such notions as 'security', 'national security', 'food security'. The author provides interpretation of the term 'food security' as ability of the country irrespective of international situation to provide all layers of the population with an access to safe, high- quality food in the amount necessary for active and healthy life without cutting state food reserves.